1996
DOI: 10.1093/pasj/48.5.671
|View full text |Cite
|
Sign up to set email alerts
|

Uniformity in the Temperature and Metallicity of the X-Ray Emitting Gas in the Abell 1060 Cluster of Galaxies

Abstract: The results from ASCA observations of the Abell 1060 cluster of galaxies are presented. Spatially sorted X-ray spectra were used to derive the distributions of the temperature and metallicity in the X-ray emitting gas of the cluster. Within ~ 20' (or 400 kpc assuming HQ = 50 km s _1 Mpc -1 ) of the cluster center, the gas temperature has been found to be radially constant at 3.1ÌQ'5 keV (or 3.1 ± 0.2 keV within ~ 10'), and the 2-10 keV luminosity was estimated to be 2 x 10 43 erg s _1 . An upper limit on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
22
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 22 publications
(29 reference statements)
6
22
0
Order By: Relevance
“…This is quite unlikely for a relaxed or nearly relaxed cluster as it is the Hydra cluster (e.g. Tamura et al 1996Tamura et al , 2000Yamasaki et al 2003).…”
Section: Depth Of the Hydra Clustermentioning
confidence: 99%
“…This is quite unlikely for a relaxed or nearly relaxed cluster as it is the Hydra cluster (e.g. Tamura et al 1996Tamura et al , 2000Yamasaki et al 2003).…”
Section: Depth Of the Hydra Clustermentioning
confidence: 99%
“…A1060 (Hydra I cluster, z = 0.0114) is an X-ray bright cluster of galaxies and is considered to be the archetype relaxed system. The ASCA and ROSAT observations of the cluster (Tamura et al 1996(Tamura et al , 2000 showed that the temperature of the ICM is constant at kT = 3.1 +0.3 −0.5 keV 1 with the X-ray luminosity L X = 2 × 10 43 erg s −1 in the 2-10 keV band. An upper limit for the flux of the cool component assuming kT = 1 keV is 6 × 10 41 erg s −1 in the energy band 0.5-3 keV.…”
Section: Introductionmentioning
confidence: 99%
“…Abell 1060 (at a redshift of z= 0.011), with a relatively circular shape [10], is by far the best studies non-cD cluster. In addition to early ASCA results [6], recent observations of this object, with Chandra [11], XMM-Newton [12], and Suzaku [13], revealed that its ICM is nearly isothermal at ~ 3.4 keV over the central region within ~75 kpc, with a mild outward temperature decrease. Given this, it is important to examine other non-cD clusters in comparison with Abell 1060 on one hand, and with cD clusters on the other hand.…”
Section: Introductionmentioning
confidence: 72%
“…These include the presence of a bright cool ICM component, a clear central enhancement in the X-ray surface brightness [3], and an increased ICM metallicity. Although these phenomena were once interpreted as evidence of cooling flows [3], the interpretation was thoroughly changed by observations with ASCA [4], and with subsequent X-ray missions [5][6][7]. The central ICM temperature decrease in these objects is now understood as a result of the stable co-existence of hot and cool plasma [8], and the central excess brightness is considered to reflect hierarchical potential shapes around cD clusters [7,9].…”
Section: Introductionmentioning
confidence: 99%